The Study of Herbicide Kinds and Tillage Methods on the Growth and Yield of Mung Bean (Vigna radiata L) - Supriyadi Supriyadi (Caraka Tani: Journal of Sustainable Agriculture, 2004)
The objective of this research was finding the answer to comprehend the influence of herbicide kinds, tillage methods, and interaction between them on the growth and yield of mung bean (Vigna radiata L). The thinking background of this research is that mung bean is not tolerant with weed competition, meanwhile herbicide that can control weed on mung bean crop hasn’t been found yet. Sometimes tillage is need to control weed, too. But the effect of tillage on increasing the yield of mung bean hasn’t been completely recognized.The research was carried out in Karangasem village, Surakarta, in about 106 meter height sea level water, at Entisol soil. The research was designed with Randomized Completely Block Design (RCBD) that arranged according to Split Plot Design, that had 2 factors with 12 treatment combinations and every combination was replicated 4 times. The first factor was tillage method as main plot, that had 3 levels as follow: no-tillage method (P0), one time tillage method (P1), and two times tillage method (P2). The second factor was herbicide kind as sub plot, that had 4 levels as follows: control (H0), Isopropylamine Glyphosate herbicide/Roundup (H1), Oxadiazone herbicide/Ronstar 250 EC (H2), and Oxyfluorfen herbicide/Goal 2E (H3). The result was analyzed with Analysis of Variance on 1% and 5% level and then analyzed with Least Square Design (LSD) test if Anova test showed significant result.From the result of this research, we can concluded that Roundup is able to increase total mature pods and dry seed weight of mung bean, but not significantly affecting all other research variables. Goal and Ronstar can make the plant height and fresh plant biomass of mung bean lower, and not significantly affecting total mature pods, total immature pods, total unfilled pods, dry seed weight, and 100 dry seed weight of mung bean. Meanwhile Ronstar is not significantly affecting. Goal can make the dry plant biomass of mung bean lower. The tillage method treatments and interaction between tillage method and herbicide kind treatments is not significantly affecting all studied variables.